Siapa bilang Sunni Syi'ah tidak bisa bersatu : debat terkini dua guru besar, Prof. Dr. Ahmad al-Ghamidi & Prof. Dr. Muhammad al-Qazwini - al-Ghamidi, Ahmad bin Sa'ad (Jakarta : Darul Haq, 2009)
On Shiah and Sunnites.
In Indonesian.
Keywords: Sunnites -- Relations -- Shi'ah.; Shi'ah -- Relations -- Sunnites; Islamic sects